Optimal Financing Structure For A Coal Hauling Road Project: A Comparative Analysis Of Corporate Finance And Project Finance At Pt Atlas Resources Tbk - Vinsensius Paul Goodman; Ana Noveria (Utan Kayu Publishing, 2026)
The thesis discusses the strategic financing dilemma of the H3 Segment Hauling Road Project at PT Atlas Resources Tbk, which is considered vital to eliminate dependence on third-party roads. The issue lies in deciding between funding the project using internal resources under Corporate Finance or using external resources through the implementation of Project Finance with a Build-Operate-Transfer (BOT) scheme in a private-to-private partnership. Accordingly, this research applies the financial valuation and risk analysis, and then compares the results to determine which scenario is better at providing a superior risk-adjusted value to the company. The study applies a quantitative method, with capital budgeting techniques as the main analytical tool. The analysis is made on the foundation of Discounted Cash Flow (DCF) valuation, which is complemented by sensitivity analysis, scenario analysis, and Monte Carlo simulation. The results confirm the financial feasibility of both scenarios. Corporate Finance scenario gives a higher Net Present Value (NPV) of Rp 1,243 billion and an Internal Rate of Return (IRR) of 48,33%. On the other side, Project Finance (BOT) scenario offers a slightly lower NPV of Rp 1,183 billion, but provides risk isolation by managing construction and operational risks to the SPV. The research concludes that the Project Finance (BOT) system is the best option. The difference in financial value (about 4,8%) is considered as a trade-off for the benefits of risk segregation at the project level, which enhances the parent company’s financial flexibility and limits its exposure to project-specific risks. It is therefore recommended that PT Atlas Resources Tbk proceed with the BOT model as there should be a properly organized concession agreement on transfer of the assets.